THE EFFECT OF FOOD CERTIFICATION ON COMPETITIVENESS AND INCREASING SALES OF AGROINDUSTRIAL PRODUCTS IN EAST JAVA - Riana, Fitria Dina (Socio-Economics/Agribusiness Department, 2024)
Food safety, which is realized through P-IRT and halal certification, must be fulfilled by producers even though it is still on a household scale. This is because food safety is a guarantee provided by producers and a right that must be obtained by consumers. Where later this certification can affect sales and also the competitiveness of existing products, this research examined MSMEs in East Java and there were 50 respondents used. Based on the research results, it is known that food certification which is realized through P-IRT and is also halal has a positive and significant influence on sales and competitiveness of the food products produced. Likewise with the knowledge of MSME producers regarding sales and product competitiveness.